Impact of Job Environment on Performance of Private School Teachers in Birendranagar - Khanal, Rishi (Journal of Entrepreneurship & Management Studies, 2024)
Many researchers claim that competencies and thus performance of teachers depend upon their attitude towards job related factors experienced by them. However, this relationship is unknown in out context. This study thus explores if the attitudes and satisfaction of the teachers working in private schools of Birendranagar toward salary, work policy, social environment, career development opportunity and work life balance have any relationship with job performance. This research uses multiple regression analysis to arrive at the conclusion based on the data collected from 104 samples of teachers from thirteen private schools who were selected using convenient sampling method. Survey was done using a questionnaire developed after review of the literature in national and international contexts. Performances of the samples were established based on the rating by the principals of the respective schools on different relevant dimensions. We found that salary had significant impact on the performance whereas the other independent variables–work policy, social environment, career development opportunities and work life balance were not found having significant relationship on job performance. This study helps the school principals and administrators understand a roadmap for good performance management and build performance oriented culture by ensuring positive workplace experience in employees. If the guidelines has word limitation, do accordingly. If not around 200 words is okay.